The influence of social media communication on climate change on public awareness in Latin America and lessons for Vietnam - Ta Van Viet; Chu Duc Ha; Phan Thuy Linh; Vu Thi Minh Tam (Journal of State Management, 2025)
Social media exerts a substantial influence on public perceptions of climate change by disseminating information and shaping attitudes. These platforms enable a rapid circulation of scientific research, news, and awareness-raising campaigns, which enhance public understanding of climate issues. This study examines the impact of social media on climate change awareness in Latin America and identifies lessons that may be applied to Vietnam. The findings show that higher levels of education, access to accurate scientific information, and the use of platforms such as YouTube and Twitter are important factors in improving public awareness and concern about climate change. Although demographic and national differences exist within the region, social media has broadened the space for public exchange and discussion, including exposure to conflicting viewpoints, which encourages more active public engagement in climate-related discourse. For Vietnam, the study highlights the importance of recognizing and effectively utilizing social media as a key component of climate change communication and response strategies.